Implementation of Character Education at SD Muhammadiyah 11 Randegan during the Covid 19 Pandemic - Elok Munjiati Ninda; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study aims to describe the values of character education in SD Muhammadiyah 11 Randegan. This research is a descriptive qualitative research. Research data sources consist of informants, and documents. Data collection techniques used in this study were (1) observation (2) interviews with teachers at SD Muhammadiyah 11 Randegan (3) Documentation. The analysis uses interactive analysis techniques which include four components, namely data collection, data reduction, data presentation, and drawing conclusions. Teachers at SD Muhammadiyah 11 Randegan already have a way of applying for character education from an early age for student discipline because character education does not only teach about science, but also plays an important role in shaping the character of students who will become the nation's successors. The function of character education is to develop the potential to become a person who has a good heart, behaves well, thinks well, and improves the nation's civilization to become a competitive person in the association.